Phase change solvents for post-combustion CO2 capture: Principle, advances, and challenges - Zhang, Shihan; Shen, Yao; Wang, Lidong; Chen, Jianmeng; Lu, Yongqi (Applied energy, 2019)
•Both liquid–solid and liquid–liquid phase change solvents critically reviewed.•Various mechanisms triggering phase separations in solvents elucidated in detail.•Advantages and challenges of phase change processes for CO2 capture assessed.•Gaps between state-of-the-art and ideal solvents analyzed.•Insights into research needs regarding solvents and desired properties provided. Carbon Capture and Storage is regarded as an important component in a portfolio of low-carbon energy technologies for mitigating climate change. Absorption technologies are presently the most available and effective approach for post-combustion CO2 capture. However, state-of-the-art amine-based absorption technologies incur intensive energy use, as high as 3 times the thermodynamic minimum, thus resulting in prohibitively high costs. Solvents are key to the performance of absorption technologies. Recently, a new class of solvents, phase change solvents, have attracted growing interest due to their potential to substantially reduce energy use for CO2 capture. Phase change solvents are homogeneous (single-phase) solvents under normal conditions, but undergo a phase transition into a heterogenic (two-phase) system, triggered by changes in polarity, hydrophilicity, ionic strength, or hydrogen bond strength to form a CO2-lean liquid phase and a CO2-enriched liquid or solid phase. This review paper first examines different mechanisms that trigger phase separations in solvents. A comprehensive list of phase change solvents reported in the recent literature, including those subject to chemically or thermally triggered phase changes, non-aqueous or aqueous systems, and those forming either a CO2-enriched solid or a liquid phase are provided and their physiochemical properties for CO2 capture are discussed. Enabled by phase change solvents, different variants of CO2 absorption processes have been developed and tested in laboratory or pilot scales over the past ten years. The status of such emerging processes is summarized and their advantages and challenges for post-combustion CO2 capture are reviewed and commented. Solvent properties such as CO2 loading capacity, lean- and rich-phase partition, desorption pressure, absorption kinetics, viscosity, stability, and volatility are critical for both CO2 capture performance and scalability. Gaps between state-of-the-art and ideal solvents are analyzed, and insights into the research needs such as solvent structure–property–performance relations, computational solvent design, ideal vapor-liquid equilibrium behavior, and integration of capture processes with post-combustion emission sources are provided.